Spike protein recognition of mammalian ACE2 predicts the host range and an optimized ACE2 for SARS-CoV-2 infection - Luan, Junwen; Lu, Yue; Jin, Xiaolu; Zhang, Leiliang (Biochemical and biophysical research communications, 2020)
SARS-CoV-2 causes the recent global COVID-19 public health emergency. ACE2 is the receptor for both SARS-CoV-2 and SARS-CoV. To predict the potential host range of SARS-CoV-2, we analyzed the key residues of ACE2 for recognizing S protein. We found that most of the selected mammals including pets (dog and cat), pangolin and Circetidae mammals remained the most of key residues for association with S protein from SARS-CoV and SARS-CoV-2. The interaction interface between cat/dog/pangolin/Chinese hamster ACE2 and SARS-CoV/SARS-CoV-2 S protein was simulated through homology modeling. We identified that N82 in ACE2 showed a closer contact with SARS-CoV-2 S protein than M82 in human ACE2. Our finding will provide important insights into the host range of SARS-CoV-2 and a new strategy to design an optimized ACE2 for SARS-CoV-2 infection. •Pets (dog and cat), pangolin and Circetidae remained the key residues for association with S from SARS-CoV and SARS-CoV-2.•The interface of the interaction between cat/dog/pangolin/Chinese hamster ACE2 and SARS-CoV/SARS-CoV-2 RBD was simulated.•N82 of ACE2 showed a closer contact with SARS-CoV-2 S than M82, suggesting an optimized ACE2 for SARS-CoV-2 infection.